THE USE OF MICROSATELLITE MARKERS TO STUDY GENETIC DIVERSITY IN INDONESIAN SHEEP - Jakaria, J.; Zein, M.S.A.; Sulandari, S.; Subandriyo, S.; Muladno, M. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The purpose of this research was to study genetic diversity in Indonesian sheep population usingmicrosatellite markers. A total of 18 microsatellite loci have been used for genotyping Indonesian sheep.Total sheep blood 200 samples were extracted from garut sheep of fighting and meat types, purbalinggasheep, batur sheep and jember sheep populations by using a salting out method. Microsatellite loci datawere analyzed using POPGENE 3.2 software. Based on this study obtained 180 alleles from 17microsatellite loci, while average number of alleles was 6.10 alleles (6 to 18 alleles) from fiveIndonesian sheep populations (garut sheep of fighting type, garut sheep of meat type, purbalingga sheep,batur sheep and jember sheep population). The average of observed heterozygosity (Ho) and expectedheterozygosity (He) values were 0.5749 and 0.6896, respectively, while the genetic differentiation forinbreeding among population (FIS), within population (FIT) and average genetic differentiation (FST)were 0.1006, 0.1647 and 0.0712, respectively. Genetic distance and genetic tree showed that Indonesiansheep population was distinct from garut sheep of fighting and meat types, purbalingga sheep, batursheep and jember sheep population. Based on this results were needed a strategy for conservation andbreeding programs in each Indonesian sheep population.